PEMBERDAYAAN UMKM BERBASIS KEARIFAN LOKAL DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DESA KUTUH KECAMATAN KUTA SELATAN KABUPATEN BADUNG - Fahmi Tanjung; I Made Sujana; Yoviniani Yevri Yanseni; Ni Luh Wulani Parwati (Nusantara Hasana Journal, 2024)
This community service program aims to increase the income of the people of Kutuh Village, South Kuta District, Badung Regency, through empowering Micro, Small, and Medium Enterprises (MSMEs) based on local wisdom. The potential of Kutuh Village's culture, traditions, crafts, and local products are the main capital in developing community businesses. According to Hidayati (2019), empowering MSMEs that utilize local advantages can create added economic value while maintaining the community's cultural identity. Community service activities are carried out through training in business management, product development, digital marketing, and business mentoring. The results of the activities show an increase in the capacity of MSME actors in business management, marketing, and product innovation, thus contributing to increasing village community income.